2018
DOI: 10.1371/journal.pone.0194688
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model for evaluation of efficacy and concomitant toxicity of anti-human CXCR4 therapeutics

Abstract: The development of therapeutic monoclonal antibodies through mouse immunization often originates drug candidates that are not cross-reactive to the mouse ortholog. In such cases, and particularly in oncology, drug efficacy studies are performed on human tumor xenografts or with “surrogate” anti-mouse ortholog antibodies if targeting tumor host cells. Safety assessment of drug candidate(s) is performed at a later development stage in healthy non-human primates. While the latter remains necessary before a drug a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…Their optimal ADC, ADC 713, was a low-affinity humanized IgG1 antibody with reduced Fc-mediator effector function. Tolerability and safety studies performed in a human CXCR4 knock-in mouse model ( 127 ) revealed significant decreases in the numbers of circulating neutrophils and monocytes 3 days after the third injection of ADC 713. Although the numbers of bone marrow lineage-negative/Sca-positive/Kit-positive (LSK) cells and HSPCs were unchanged, there was a significant decrease in granulocyte-monocyte progenitors, suggesting some hematopoietic toxicity.…”
Section: Targeting Cxcr4 With Antibody-drug Conjugatesmentioning
confidence: 99%
“…Their optimal ADC, ADC 713, was a low-affinity humanized IgG1 antibody with reduced Fc-mediator effector function. Tolerability and safety studies performed in a human CXCR4 knock-in mouse model ( 127 ) revealed significant decreases in the numbers of circulating neutrophils and monocytes 3 days after the third injection of ADC 713. Although the numbers of bone marrow lineage-negative/Sca-positive/Kit-positive (LSK) cells and HSPCs were unchanged, there was a significant decrease in granulocyte-monocyte progenitors, suggesting some hematopoietic toxicity.…”
Section: Targeting Cxcr4 With Antibody-drug Conjugatesmentioning
confidence: 99%
“…6c). In our orthotopic in vivo models, mouse CXCL12 activates human CXCR4 8,12 and most MM cells are found in the bone marrow. The serum CXCL12 levels in tumour-naïve NSG mice average those of wild type, tumour-naïve Balb/c mice (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Besides haematopoietic progenitors, CXCR4 is expressed in leukocytes and other normal adult quiescent tissues (kidney tubular epithelium and adrenal gland) 6,8,42,43 . We reasoned that a payload class whose mechanism of action (MoA) involves blocking cell division would enhance the TI of an anti-CXCR4 ADC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations